Impacto do pregão eletrônico nas economias das licitações da Secretaria da Saúde do Estado do Ceará - Wirtzbiki, Josane Botelho Vieira (2010)
The present dissertation addresses one of the most important themes in the area of public bids in Brazil, the electronic bidding. It expectative that change by a structure of traditional bidding, based at invitation and taking from price, for the electronic bidding improve an efficiency the contractions and produce biggest economy to publics cofferes. This hypothesis is test in this work utilizing whether basic fact extract of bids having how beneficent the Secretariat the Health the State the Ceará. Three models of linear regression multiple were used not only for to test the hypothesis what a change the modality bring more economy for government, but also for to identify what factores influenced in the differentiate between price the reference and price the contraction. The results the electronic bidding show one increase in the mean economy varing between 25 and 31 points percentage when compare with the traditional bidding.